An escalating treatment strategy for children with severe chronic immune thrombocytopenia: Preliminary report from a single center. Issue 6 (15th March 2021) - Fu, Lingling; Ma, Jie; Gu, Hao; Ma, Jingyao; Wei, Yunyun; Chen, Zhengping; Wu, Runhui
Abstract: Objective: To analyze the effects of escalating treatment strategy in children with severe chronic immune thrombocytopenia (SCITP). Methods: This was a single‐center, retrospective cohort study. Data from children with SCITP who received escalating treatment strategy in our center were collected between June 2017 and August 2019. The escalating strategy included three steps: Step I (six courses of high‐dose dexamethasone [HDD]), Step II (HDD combined with low‐dose rituximab), and Step III (eltrombopag). Results: A total of 30 cases (18 males and 12 females) were included, with duration of immune thrombocytopenia (ITP) of 20.5 (12.0–96.0) months. After treatment, the remission rate was 36.7% (11/30) and the sustained response (SR) rate was 68.2% (15/22). The distribution (remission rates) from Step I to III was as follows: nine of 30 (33.3%, 3/9); four of 30 (50%, 2/4); 17/30 (29.4%, 5/17), respectively. In eltrombopag (Step III) cases, 47.5% (8/17) maintained a platelet count of ≥50 × 10 9 /L, 37.5% (3/8) had dose tapering, and 25% (2/8) have successfully discontinued the medication. The number of patients at 12, 24, and 36 months were 30, seven, and two, with a total response and remission rates of 80% (36.7%), 57.1% (28.6%), and 50% (50%), respectively. The total relapse rate was 26.7% (8/30), and three cases from Step II and five cases from Step III. Conclusion: The escalating strategy for children SCITP showed an effective improvement rate with 36.7% remission and 68.2% SR, and 30% could benefit and retain SR from HDD treatment. Combined treatment with eltrombopag can reduce the relapse rate of low‐dose rituximab.